1954
DOI: 10.1111/j.1540-4560.1954.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

The NORC Studies of Human Behavior in Disaster

Abstract: The Analysis of DeterminantsInvestigation of reactions to disaster are mainly motivated by the need for information relevant to the prediction and control of behavior of populations exposed to the extreme stresses to be anticipated in war-time. Knowledge in this field is, obviously, of the highest importance. There are, however, very serious difficulties in obtaining valid and reliable information.1 The studies reported in this paper are the product of a research team whose composition varied over time. Substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
1

Year Published

1967
1967
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(80 citation statements)
references
References 0 publications
7
72
0
1
Order By: Relevance
“…More specifically, Boudia and Jas [45] acknowledged that researchers reacted strongly to the publication of Beck's book, documenting what seems to have been blind spots in the book, namely, citizen science, public participation in scientific research (PPSR), and the role of concerned individuals in shaping the definition of risk. Indeed, in more than 50 years of fieldwork [49][50][51][52][53], 6 social scientists working on risk and disaster studies have shown that, when examined in detail, the conditions for the emergence of a risk and the characterization of a disaster, rather than being a homogeneous set of concepts, practices, and methods, have "been continually fraught with internal tensions" [55].…”
Section: A Brief Overviewmentioning
confidence: 99%
“…More specifically, Boudia and Jas [45] acknowledged that researchers reacted strongly to the publication of Beck's book, documenting what seems to have been blind spots in the book, namely, citizen science, public participation in scientific research (PPSR), and the role of concerned individuals in shaping the definition of risk. Indeed, in more than 50 years of fieldwork [49][50][51][52][53], 6 social scientists working on risk and disaster studies have shown that, when examined in detail, the conditions for the emergence of a risk and the characterization of a disaster, rather than being a homogeneous set of concepts, practices, and methods, have "been continually fraught with internal tensions" [55].…”
Section: A Brief Overviewmentioning
confidence: 99%
“…Although panic does occur it is the exception and mostly limited to few individuals. Panic requires specific conditions: A strong thread towards the individual existence in combination with vanishing opportunities to escape whereby time is a crucial factor (Fritz and Marks, 1954;Drabek, 1969;Rosengren et al, 1975;Houts et al, 1984). The more time available, the larger is the influence of social norms and, consequently, the more pro-social evacuees' behavior (Frey et al, 2011).…”
Section: Within-day Replanning Of Exceptional Eventsmentioning
confidence: 99%
“…If separated at the time the evacuation order is announced they rather prefer to meet within the evacuation zone than leaving individually (Fritz and Marks, 1954;Drabek, 1969;Kiefer et al, 2009). In terms of socio-demographics, women and children are more likely to participate in an evacuation than men (Houts et al, 1984;Johnson and Zeigler, 1986;Houts et al, 1988;Efrat, 1992).…”
Section: Within-day Replanning Of Exceptional Eventsmentioning
confidence: 99%
“…Heavy air attacks of civilians characteristically bring an increase in temporary emotional shock involving anxiety states, reactive depressicn, or apathy (21,39,40).…”
Section: Prevalence Of Psychological Disordersmentioning
confidence: 99%
“…Where one of the defining properties of panic is the absence of apparent routes of escape (Janis, 39 ; Demerath,15), it would seem that panic is being thought of primarily as terror. But • where one of the defining properties of panic is the belief inthe presence of temporary routes of escape (Chapman,14;Fritz and Marks,21;Quarantelli,65;Williams,84), it would seem that panic is being thought of primarily as flight.…”
mentioning
confidence: 99%